The Role of Endostatin in Rheumatoid Arthritis - Nijhawan, Priya; Behl, Tapan (Current Rheumatology Reviews, 2021)
Background: Endostatin by its therapeutic value against rheumatoid arthritis has recently gained significant interest in biomedical science. A recent study revealed that various approaches have been made to prevent rheumatoid arthritis by either controlling or inhibiting the progression of angiogenesis. Objective: The main objective of the current manuscript is to enumerate the intrinsic role of endostatin in rheumatoid arthritis. Methods: A thorough and detailed review of literature from the papers published from the year 1997-2019 was studied for the preparation of the current article. Results: Endostatin is one such agent of the subfamily of ECM called as multiplexins obtained from proteolytic cleavage of XVIII and its carboxylic terminal fragments and is known for its antiangiogenic and antiproliferative property. The exact mechanism of endostatin is still unclear, but it acts by downregulating or inhibiting the responses of various factors, including Id1, Id3, matrix metalloproteinase, and Nuclear factor Kappa B that are liable for angiogenesis. The mutual effects on adipogenesis and angiogenesis, endostatin inhibits dietary-induced obesity and its related metabolic disorders, such as insulin resistance, glucose intolerance, and hepatic steatosis. Conclusion: The present review demonstrates the intrinsic usage of endostatin as a novel molecule in rheumatoid arthritis. It focuses on the status of the therapeutic potential of endostatin in inhibiting the activity of angiogenesis is also very well explored.
Keywords: obesity